CORRELATION OF PLASMA ENDOTHELIN-1 LEVELS WITH PULMONARY HYPERTENSION AFTER INHALED NITRIC OXIDE THERAPY - Razzaq, Zubia; Hussain, M, Mazhar; Naqvi, Shahab; Aslam, Mohammad (Journal of Ayub Medical College Abbottabad, 2009)
Background: Variable response to inhaled nitric oxide (iNO) therapy in patients with mitral stenosis (MS) having pulmonary hypertension (PH) has been documented in early studies. The objectives of this study were to measure plasma Endothelin-1 (ET-1) levels in those patients and to correlate them with pulmonary vascular indices after iNO therapy. It was Quesi-experimental study. Methods: Thirty patients with mitral or mixed mitral and aortic valve disease with severe pulmonary hypertension and enrolled for valve replacement surgery were included. Before the replacement, baseline pulmonary vascular indices and cardiac output were recorded. After the surgery, 10-20 ppm iNO was administered for 1 hour and all the parameters were again recorded. Patients were grouped into responders and non responders on the basis of % reduction in Pulmonary Vascular Resistance (PVR) after iNO therapy. Plasma ET-1 levels were measured in both groups by ELISA before and after the iNO therapy. Paired sample t-test was used to compare mean values for significance. The correlations between variables were then calculated by using Pearson’s coefficient. Results: The plasma ET-1 levels were very high in all patients. They reduced in responders after iNO therapy; non-responders paradoxically showed significant increase in the levels of ET-1 after iNO therapy. Moreover, a positive correlation was observed in plasma ET-1 levels and post operative levels of PVR. Conclusion: The correlation of changes in PVR and plasma ET-1 levels in responders suggests that high plasma ET-1 is a key mediator of poor response in PH secondary to MS, after iNO therapy. Keywords: Mitral Stenosis, Pulmonary Hypertension, Inhaled Nitric Oxide